Evolution of Late Wintertime Thermally Driven Local Flows and Temperature Fields over Far-Western Nepal - Regmi, Ram P.; Maharjan, Sangeeta (Journal of Institute of Science and Technology, 2016)
Atmospheric processes over the Himalayan complex terrain are yet to be studied extensively. Only a few significant researches are reported from this region and the Far-Western Region (FWR) of Nepal still remains untouched. Thus, the present study was conceived to understand the meteorological flow characteristics and thermal environment over the region and associated areas during the late wintertime with the application of the state-of-the-art-of Weather Research and Forecasting (WRF) Modeling System. The study revealed that the northern mountainous region developed strong down slope wind during the night and morning times, which sweeps out the southern plain area of Nepal and may reach just beyond the border. The wind over the plain was very shallow whose depth was just about 100 m. The down slope winds over the southern slope of the Daijee and Nandhaur mountain ranges were significantly enhanced by the subsidence of the southerly wind that prevails above 1 km height above the mean sea level. Close to the noon time a very gentle southerly valley wind from the southern plain replaced the nighttime down slope. Very shallow but strong surface inversion builds up over the plain that breaks up in the late morning. The depth of the mixed layer and the valley wind may reach up to 1km in the afternoon. The thermal environment over the FWR of Nepal was fairly hot that may remain around 35°C in the afternoon around the Mahendranagar area whereas the temperature during the nighttime may go as low as 23°C. The study revealed that, contrary to the general perception, temperature over plain areas of Nepal was significantly higher than further southern areas belonging to India. The meteorological flow fields over the FWR of Nepal executed diurnal periodicity with little day-to-day variation during the late wintertime. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 35-47